ETIKA PEMIMPIN POLITIK DALAM KITAB KUMPULAN RINGKAS BERBETULAN LEKAS (PERSPEKTIF MAQASHID AL-SYARIAH) - Abd Rahman (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Abstract: The leader has the power to govern the country with the responsibility of providing welfare, peace and tranquility. However, the power can also be bad if it is misused. This article intends to discuss the ethics of political leaders in Raja Ali Kelana's Kumpulan Ringkas Berbetulan Lekas (KRBL) from the perspective of maqashid al-syari'ah. The manuscript which is the realm of Malay scholarship is analyzed with a content analysis approach. From the study, this work was born from the background of political and religious events that existed on Penyengat Island at that time. This KRBL is written briefly but has the essence of a scientific message for each mastery. The results of this study, it can be seen that five important points in the ethics of power must be guarded by state leaders, namely maintaining religion and the state, being fair, welfare of the people, loyal and dedicated and maintaining togetherness and unity. According to Raja Ali Kelana, it is very important for every leader to uphold the normative ethical values of religion because power can easily lead to slipping into wrongdoing. From the analysis, this concept is in line with the ethics of power which is based on maqashid al-syari'ah. So it is very natural that the concept of power ethics idealized by Raja Ali Kelana is also called the maqashidi power ethic, which is an ethic that refers to the spirit of the values of maqashid al-sharia. Keywords: The ethics of Maqashidi; the ethics of power; Malay Manuscript; raja ali kelana